Autoimmune haemolytic anaemia and immune thrombocytopenia following SARS‐CoV‐2 and non‐SARS‐CoV‐2 vaccination: 32 Years of passive surveillance data. (23rd December 2022) - Jacobs, Jeremy W.; Booth, Garrett S.; Guarente, Juliana; Schlafer, Danielle; Zheng, Leon; Adkins, Brian D.
Summary: Autoimmune haemolytic anaemia (AIHA) and immune thrombocytopenia (ITP) are two uncommon haematologic autoimmune conditions that can rarely arise secondary to vaccination. Prior studies using the US Centers for Disease Control's (CDC) Vaccine Adverse Event Reporting System (VAERS) have demonstrated this infrequency, but contemporary data as well as comparison with current information regarding SARS‐CoV‐2 vaccination has not been assessed. In this study, we reviewed VAERS database reports from 1990 to 2022 to characterize the incidence and clinical and laboratory findings of non‐SARS‐CoV‐2‐associated AIHA and ITP and SARS‐CoV‐2 vaccine‐associated AIHA and ITP. We discovered a total of 863 AIHA and ITP reports following vaccination with 15 non‐SARS‐CoV‐2 and four SARS‐CoV‐2 vaccines submitted to the CDC VAERS database. AIHA and ITP reporting was low for both groups, with a large proportion excluded due to a lack of clinical details. ITP was reported the most frequently in both groups and was significantly more common with measles–mumps–rubella (MMR) vaccination ( p  < 0.001) in the non‐SARS‐CoV‐2 group. AIHA and ITP cases were higher in the SARS‐CoV‐2 vaccine group, though ultimately still very infrequent. Autoimmune haematologic disease is vanishingly rare after immunization and rates are lower than in the general population according to passive reporting.